2022
DOI: 10.1001/jamanetworkopen.2022.3050
|View full text |Cite
|
Sign up to set email alerts
|

Management, Surveillance Patterns, and Costs Associated With Low-Grade Papillary Stage Ta Non–Muscle-Invasive Bladder Cancer Among Older Adults, 2004-2013

Abstract: IMPORTANCE Low-risk non-muscle-invasive bladder cancer (NMIBC) is associated with extremely low rates of progression and cancer-specific mortality; however, patients with low-risk NMIBC may often receive non-guideline-recommended and potentially costly surveillance testing and treatment. OBJECTIVE To describe current surveillance and treatment practices, cancer outcomes, and costs of care for low-grade papillary stage Ta (low-grade Ta) NMIBC and identify factors associated with increased cost of care. DESIGN, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 46 publications
1
21
0
Order By: Relevance
“…Urine cytology is a non‐invasive test for the diagnosis and follow‐up of patients with BLCA; however, it has a low sensitivity for low‐grade BLCA (LG‐BLCA) 6 . Further studies revealed that the use of urine cytology could not reduce the number of cystoscopies received by patients with BLCA and also highlighted that cystoscopy and cytology are currently overused in low‐risk BLCA patients, increasing the cost of patient care 5,7 . Therefore, developing highly accurate, cost‐effective, rapid and painless methods for diagnosing, classifying and monitoring BLCA are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Urine cytology is a non‐invasive test for the diagnosis and follow‐up of patients with BLCA; however, it has a low sensitivity for low‐grade BLCA (LG‐BLCA) 6 . Further studies revealed that the use of urine cytology could not reduce the number of cystoscopies received by patients with BLCA and also highlighted that cystoscopy and cytology are currently overused in low‐risk BLCA patients, increasing the cost of patient care 5,7 . Therefore, developing highly accurate, cost‐effective, rapid and painless methods for diagnosing, classifying and monitoring BLCA are needed.…”
Section: Introductionmentioning
confidence: 99%
“…A publication [ 14 ] analysed a cohort of 13,054 patients with LG Ta NMIBC diagnosed between 1 January 2004–31 December 2014 and to find factors related to treatment costs. The results suggest that cystoscopy was used too frequently.…”
Section: Introduction: Bladder Cancer Issues and Urinary Biomarkersmentioning
confidence: 99%
“…The standard treatment for NMIBC has been transurethral resection of the bladder tumor (TURBT), with or without adjuvant intravesical instillation (IVI) of chemotherapy or bacillus Calmette-Gueŕin (BCG) therapy (3,4). However, 40%-80% of initially treated NMIBC patients experience tumor recurrence, and approximately 15% eventually progress to MIBC (5)(6)(7). The risk-scoring models developed by the European Organisation for Research and Treatment of Cancer (EORTC) (3) and the Spanish Urological Organization (Club Urologico Español de Tratamiento Oncologico, CUETO) (4) have been widely used to predict the survival and prognosis of patients with NMIBC (8,9).…”
Section: Introductionmentioning
confidence: 99%